Responsibility of Local Governments in Fulfilling the Right to Food - Mulyani Zulaeha; Lies Ariany; Rahmat Halim Sapoetra; Nabilla Nurrosyifa Azzahra (International Journal of Law, Environment, and Natural Resources, 2023)
Government Regulation Number 17 of 2015 concerning Food Security and Nutrition states that the Provincial Government, Regency/City Government, and/or Village Government implement policies and are responsible for the implementation of food security in their respective regions. Food security must be prioritized, and support from the Local Government and the Central Government in maintaining food security is important to prevent food crises. This study aims to analyze the policy of the Regional Government in managing food needs and providing food reserves so as to provide protection for the fulfillment of the right to food in South Kalimantan. Through socio-juridical research methods (socio-legal) using an interdisciplinary or "hybrid" approach between aspects of normative legal research through sociological approaches using qualitative analysis methods, it will be possible to observe the compatibility between das sollen and das sein, namely the integrity of a detailed and careful explanation of legal issues between law in book and law in action. As a form of responsibility, the Provincial Government of South Kalimantan has stipulated Regional Regulation and Regency/City Regulation as well as Regent/Mayor Regulation related to food as a legal basis in making policies/programs/activities related to food management and also providing food reserves so that communities are protected and the rights to their food are fulfilled both in quantity, quality, safe, diverse, nutritious, equitable and affordable. The regulation made is also should not contrary to the religion, beliefs, and culture of the community, so that the community and the individuals are able to live healthy, active, and productive sustainably. The government is also coordinating the agencies/SKPD Regional Government both vertically and horizontally, and carrying out cooperation about this matter with other regions.